Effect of Cassia fistula L. aqueous extract in maternal reproductive outcome, some serum indices and fetal anomaly frequency in rat - Saeed Hakiminia; Zahra Esmaeeli; Ali Akbar Moghadamnia; Seyyed Gholam Ali Jorsaraei; Farideh Feizi; Sorayya Khafri; Zahra Memariani; Hoda Shirafkan; Seyyed Ali Mozaffarpur (Caspian Journal of Internal Medicine, 2022)
Background: Cassia fistula was used traditionally as laxative in pregnant women. Nevertheless, its fetal and maternal effects in pregnancy have not been studied yet. Methods: Oral (Lethal Dose, 50%) LD50 was determined in mice. In addition, a control group, pregnant rats in other 5 experimental groups (n=12) received orally C. fistula aqueous extract (500, 1000 and 2000 mg/kg), tween80 (10%) and distilled water during pregnancy up to the delivery (21-23 days). Some serum indices were evaluated in maternal blood samples after delivery. Histopathologic and histomorphometric evaluations were performed on the selected slices of newborn rats. Results: Anthraquinone‎ content of the aqueous extract was 0.34% w/w. Oral LD50 was obtained more than 5000mg/kg. No abortions and newborn anomalies were observed in groups. The height and weight of the offspring were significantly reduced by the administration of 500, and 2000 mg/kg of extract compared to control. There was no significant change in maternal blood urea and creatinine. Higher concentration (2000mg/kg) led to ALT elevation. ALS levels decreased dose-dependency in treatment groups comparing to control. Histopathological findings showed significant lung vascular congestion, and hypertrophy of heart in group tween80, and significant hepatic parenchymal inflammation in tween80 and 2000mg/kg and 1000mg/kg groups. In all tissues of all groups, malpighian body area and bowman’s capsule space significantly increased compared to the control group. Conclusion: It seems C. fistula extract is safe in pregnancy. Because of confounding role of tween80 in histopathological finding, more research is necessary.